Differential regulation of mycelial growth and aflatoxin biosynthesis by Aspergillus flavus under different temperatures as revealed by strand‐specific RNA‐Seq. Issue 10 (22nd July 2019) - Han, Guomin; Zhao, Kai; Yan, Xiaodan; Xiang, Fangzhi; Li, Xuede; Tao, Fang
Abstract: Although several regulatory pathways have been reported for Aspergillus flavus, the regulation of aflatoxin production and mycelial growth under different temperatures remains unclear. In this study, A. flavus differentially expressed genes (DEGs) and regulatory pathways were analyzed under three temperatures, by strand‐specific RNA‐Seq. Results show that a total of 2, 428 and 1, 474 DEGs were identified in fungal mycelia cultured at 20°C and 37°C, respectively, as compared with the control (28°C). Approximately 79% of DEGs in the 37°C samples were up‐regulated genes, while 63% of DEGs in the 20°C samples were down‐regulated genes. Most of the DEG pathways enriched by lower temperatures differed from those enriched by higher temperatures, while only a small portion of the pathways were shared by A. flavus grown under different temperatures. Aflatoxin biosynthesis, Butanoate metabolism, oxidation–reduction process, and benzene‐containing compound metabolic process were the shared down‐regulated pathways, while steroid biosynthesis, oxidoreductase activity, cellular protein modification process, DNA binding, protein complex were the shared up‐regulated pathways between lower and higher temperatures. The shared genes and pathways are the key regulatory candidates for aflatoxin biosynthesis with changes of temperature. In addition, the identification of both up‐regulated and down‐regulated genes provides a useful gene set for further investigation of the aflatoxin biosynthesis among Aspergillus . Abstract : Previous studies proposed that fungal growth and aflatoxin biosynthesis possibly regulated by PKa pathway. However, our result indicated that aflatoxin biosynthesis and fungal mycelia growth of A. flavus under different temperatures should be regulated by different pathways. In addition, the identification of both up‐regulated and down‐regulated genes provides a useful gene set for further investigation of the aflatoxin biosynthesis among Aspergillus.